Riwayat Status Gizi Ibu Hamil, Berat Badan dan Panjang Badan Lahir dengan Kejadian Stunting di Desa “T” Wilayah Kerja PKM “M”, Lebak – Banten. - Syifa Fauziah; Aminah Muin (Jurnal Obstretika Scientia, 2021)
Stunting describes chronic undernutrition during growth and development from early life. This situation is represented by a height-for-age (TB/U) z-score of less than -2 standard deviations (SD) based on WHO growth standards. The purpose of this study was to determine the relationship between the history of nutritional status of pregnant women, birth weight and length with the incidence of stunting in toddlers in the village of "T" in the working area of Puskesmas "M". The type of research used is case control research. The population in this study were all mothers who had toddlers in the village of "T", totalling 620 toddlers. The sample taken was 44 mothers who had toddlers for each case and control group. Data analysis using chi square test. The results showed that there was no significant relationship between the history of nutritional status of pregnant women (p=0.472), body weight (p=0.488) and birth length (p=1.000) with the incidence of stunting. This is due to the high awareness of mothers to participate in posyandu every month, so that stunting is easily detected quickly and health workers immediately make prevention and treatment efforts by providing additional food. Maternal nutrition needs to be considered through monitoring the nutritional status of mothers during pregnancy through ANC and monitoring and improving child nutrition after birth, namely the First 1,000 Days of Life (HPK).